GE_GERICHTE P/5070/2012 vom 25. Februar 2015 - GE Cour de justice (2015)
PEINE PÉCUNIAIRE; LÉSÉ; SURSIS À L'EXÉCUTION DE LA PEINE; ABUS DE POUVOIR; FIXATION DE LA PEINE | CP.312; CPP.118.1; CPP.115.1; CP.47; CP.34; CP.42